Edukasi Pencegahan dan Manfaat Mc Kenzie Exercise dalam Mengurangi Nyeri Punggung Bawah pada Guru SMP Negeri 2 Seputih Mataram Lampung Tengah - Angga Pradipta; Nungki Marlian Yuliadarwati (Universitas Maritim AMNI Semarang, 2025)
Introduction: Low back pain (LBP) is pain felt in the lower back area, either local pain or radicular pain or both. This pain is felt between the lower rib angle to the buttocks, namely in the lumbar or lumbosacral area and is often accompanied by pain spreading towards the legs. Purpose: This education aims to explain the prevention and benefits of Mc. Kenzie exercise in reducing lower back pain that can be done independently to prevent ongoing pain. Method: The method used is to educate teachers by practicing directly and promotional media in the form of leaflets to make it more attractive and easy to understand. Results: The results of the pre-test and post-test showed an increase in knowledge from an initial score of only 16% then increasing to 100%. Conclusion: Delivery of health information regarding the prevention and treatment of lower back pain by teaching how to do Mc. Kenzie exercise shows a positive impact on increasing the knowledge of teachers at SMP Negeri 2 Seputih Mataram, Central Lampung, where this exercise aims to reduce pain complaints, increase flexibility and mobility, so that teachers can handle pain complaints independently by doing exercises routinely and regularly.